Memory B Cells Induced by Sputnik V Vaccination Produce SARS-CoV-2 Neutralizing Antibodies Upon Ex Vivo Restimulation - Byazrova, Maria G.; Kulemzin, Sergey V.; Astakhova, Ekaterina A.; Belovezhets, Tatyana N.; Efimov, Grigory A.; Chikaev, Anton N.; Kolotygin, Ilya O.; Gorchakov, Andrey A.; Taranin, Alexander V.; Filatov, Alexander V. (Frontiers in Immunology, 2022)
The development of effective vaccines against SARS-CoV-2 remains a global health priority. Despite extensive use, the effects of Sputnik V on B cell immunity need to be explored in detail. We performed comprehensive profiling of humoral and B cell responses in a cohort of vaccinated subjects (n = 22), and demonstrate that Sputnik vaccination results in robust B cell immunity. We show that B memory cell (MBC) and antibody responses to Sputnik V were heavily dependent on whether the vaccinee had a history of SARS-CoV-2 infection or not. 85 days after the first dose of the vaccine, ex vivo stimulated MBCs from the vast majority of Sputnik V vaccinees produced antibodies that robustly neutralized the Wuhan Spike-pseudotyped lentivirus. MBC-derived antibodies from all previously infected and some of the naïve vaccine recipients could also cross-neutralize Beta (B.1.351) variant of SARS-CoV-2. Virus-neutralizing activity of MBC-derived antibodies correlated well with that of the serum antibodies, suggesting the interplay between the MBC and long-lived plasma cell responses. Thus, our in-depth analysis of MBC responses in Sputnik V vaccinees complements traditional serological approaches and may provide important outlook into future B cell responses upon re-encounter with the emerging variants of SARS-CoV-2.